A Firefly Algorithm for Portfolio Optimization - Lazulfa, Indana (IndoMS, 2019)
Portfolio optimization is the process of allocating capital among a universe of assets to achieve better risk – return trade-off. Portfolio optimization is a solution for investors to get the return as large as possible and make the risk as small as possible. Due to the dynamic nature of financial markets, the portfolio needs to be rebalanced to retain the desired risk-return characteristics. This study proposed multi objective portfolio optimization model with risk, return as the objective function. For multi objective portfolio optimization problems will be used mean-variance model as risk measures. All these portfolio optimization problems will be solved by Firefly Algorithm (FA).